Capsular polysaccharide vaccine for Group B Neisseria meningitidis, Escherichia coli K1, and Pasteurella haemolytica A2 - Robbins, John B. (National Academy of Sciences, 2011)
We reviewed the literature that is the basis for our proposal that (2→8)-α-Neu5Ac conjugates will be safe and effective vaccines for Group B meningococci (GBMs), Escherichia coli K1, and Pasteurella haemolytica A2. Although (2→8)-α-Neu5Ac is a virulence factor and a protective antigen of these three pathogens, it is also a component of normal tissues (neural cell adhesion molecule). Natural, anti–(2→8)-α-Neu5Ac present in most adults, vaccine-induced antibodies, and even high levels of spontaneously appearing monoclonal anti–(2→8)-α-Neu5Ac did not cause autoimmunity. Although it is not possible to prove a null hypothesis, there are no epidemiologic, serologic, immunologic, or clinical data to indicate that (2→8)-α-Neu5Ac antibodies will induce pathology or an autoimmune disease. No increased pathology caused by these antibodies was found, even in neonates and infants of mothers recovered from GBM meningitis. The lack of pathology mediated by anti–(2→8)-α-Neu5Ac may be explained by different presentations of (2→8)-α-Neu5Ac on bacterial and mammalian cells and by the unusual physicochemical properties of anti–(2→8)-α-Neu5Ac. Based on clinical and experimental data collected over 30 y and because (2→8)-α-Neu5Ac is an essential virulence factor and a protective antigen for GBM, E. coli K1, and P. haemolytica A2, protein conjugates of it are easy to prepare using inexpensive and plentiful ingredients, and they would be compatible with routinely administered infant vaccines, clinical studies of these conjugates should proceed.